Efektivitas Media E-Learning Berbasis Learning Management System (LMS) Di Era Pandemi Covid-19 - Noer Ekafitri Sam; Reski Idrus (Universitas Persada Indonesia YAI, 2021)
This study aims to determine the effectiveness of e-learning media based on learningmanagement system (LMS) in the era of the covid-19 pandemic on student learning outcomes andactivities in the Information Systems study program with competence in scientific writingmethodology. The research used is a quasi-experimental (quasi-experimental) with a one grouppretest posttest design, namely experimental research carried out in one group that was chosenrandomly and no stability and clarity test of the group's condition was carried out before beingtreated. The population in this study were students majoring in Information Systems STMIK HasanSulur Wonomulyo. With a sample of 15 seventh semester students. The results obtained are (a)analysis of the N-Gain score on the pretest-posttest which is in the high category, which meansthere is a change in students' cognitive towards the implementation of the media; (b) analysis ofstudent activities in the very active category. Based on the research results obtained, the applicationof e-learning media based on the learning management system meets the effective category.Learning Management System can be used as a media reference in learning that can improvestudent learning outcomes and activities